Model Pengembangan Ekonomi Kota Malang - -, Sodik -; Mas’ud, Mukhlis; Nurhayati, Indah Dewi (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
The research aims at: (1) providing the guideline for the implementation of Economic Development Model for Malang City; (2) identifying economic potential and its relation with economic development for Malang City; (3) examining the development potential based on strategy and priority considering the economic potential of Malang City; and (4) formulating economic development model for Malang City. Taking account the results of research, it may conclude that Economic Development Model for Malang City has a potential sector. Results of input-output analysis, through forward and backward linkage, indicate that the economic activity of Malang City remains at Quadrant II involving such production activities as: metal-based goods industry, rice, other plantation-based crop, corn, truck, sugarcane, fossil oil, natural gas, trade, poultry, telecommunication, mining, upland fishery, private service and household service. Keywords: Economic Development Model, Input-Output Analysis, and Forward and Backward Linkage